1972
DOI: 10.1099/00207713-22-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacter agglomerans (Beijerinck) comb. nov. (the Herbicola-Lathyri Bacteria)

Abstract: En tero bac t er agglo m erans (Beijerinck) comb. nov. (the Herbicola-Lathyri Bacteria)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
72
1
2

Year Published

1978
1978
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(76 citation statements)
references
References 10 publications
1
72
1
2
Order By: Relevance
“…The type strain is CFBP 6631 T (=A37 T =ATCC 700880 T =CECT 5263 T ). Ewing & Fife (1971, 1972 concluded that strains isolated from clinical sources and strains belonging to the Herbicola group of Dye (1969) are the same species and referred to them as the 'Enterobacter agglomerans-Erwinia herbicola' complex. Lelliott & Dickey (1984) defined Erwinia as associated with plants as pathogens, saprophytes or constituents of the epiphytic flora.…”
mentioning
confidence: 99%
“…The type strain is CFBP 6631 T (=A37 T =ATCC 700880 T =CECT 5263 T ). Ewing & Fife (1971, 1972 concluded that strains isolated from clinical sources and strains belonging to the Herbicola group of Dye (1969) are the same species and referred to them as the 'Enterobacter agglomerans-Erwinia herbicola' complex. Lelliott & Dickey (1984) defined Erwinia as associated with plants as pathogens, saprophytes or constituents of the epiphytic flora.…”
mentioning
confidence: 99%
“…Since the early 1970s, various attempts have been made to clarify the Erwinia herbicola-Enterobacter agglomerans complex (Ewing & Fife, 1972;Gardner & Kado, 1972;Young et al, 1978;Dye, 1981;Brenner et al, 1984;Verdonck et al, 1987;Beji et al, 1988). The most comprehensive study to date was performed by Brenner et al (1984), who separated 124 strains belonging to this complex into 13 groups based on their DNA-DNA hybridization relatedness.…”
mentioning
confidence: 99%
“…Ewing and Fife (10) reported that 80% of strains belonging to the species Enterobacter agglomerans are anaerogenic, while the remaining strains are aerogenic. Biochemical studies carried out on these organisms have shown that the aerogenic strains resemble Enterobacter cloacae and other Enterobacter species more closely than they resemble anaerogenic strains (10,20). On the other hand, some biochemical characteristics of the anaerogenic strains (such as yellow pigmentation) resemble those typically associated with Erwinia species (19, 20).…”
Section: Resultsmentioning
confidence: 99%
“…These authors further classified the strains belonging to Enterobacter agglomerans into seven anaerogenic biogroups and four aerogenic biogroups. The majority of strains are anaerogenic (10,20). When the biochemical characteristics of the aerogenic and anaerogenic strains of Enterobacter agglomerans were compared with the characteristics of strains of Enterobacter cloacae, it was found that the strains belonging to the aerogenic biogroups are more similar to the Enterobacter cloacae strains than the strains belonging to the anaerogenic biogroups are (10,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation